2005
DOI: 10.1002/ca.20108
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic study of the blood supply of perioral region

Abstract: The use of flaps to reconstruct lip defects requires detailed knowledge of the local vasculature. New flaps for surgery around the mouth can be devised if the surgeon knows the distribution of the perioral arterial branches. Examination of the anatomy of perioral branches of the facial artery (FA) confirmed the consistent presence of septal and alar branches in the upper lip and a labiomental branch in the lower lip. Mucosal flaps from the upper lip based on the deep septal branch or the alar branch of the FA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
102
1
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(113 citation statements)
references
References 22 publications
(34 reference statements)
5
102
1
5
Order By: Relevance
“…This patient might have had a hypoplastic facial artery as found in 2% to 9% of the population. 11,12 There are more probable explanations to our higher rate of complications. Compared to other reports, the patients in our series are older, have a higher rate of reconstruction following locally advanced tumor resections, and have had multimodality treatments more often.…”
Section: Discussionmentioning
confidence: 85%
“…This patient might have had a hypoplastic facial artery as found in 2% to 9% of the population. 11,12 There are more probable explanations to our higher rate of complications. Compared to other reports, the patients in our series are older, have a higher rate of reconstruction following locally advanced tumor resections, and have had multimodality treatments more often.…”
Section: Discussionmentioning
confidence: 85%
“…The marginal branch of the facial nerve was identified by electric simulation and preserved. Opposite to other groups [8] we included in all patients the anterior belly of the digastric muscle in conjunction with the overlying fasciocutaneous tissue into the flap in order to preserve the terminal course of the submental vessels and perforators [9]. The transposition of the pedicled flap into the oral cavity was performed after completion of intraoral tumor resection and analysis of frozen tissue sections ( Fig.…”
Section: Patients With Submental Island (Smi-) Flapmentioning
confidence: 99%
“…Up to now, several techniques such as the application of different staining solutions and colored latex have been used to stain and demonstrate the arteries (Pavkov et al, 2004;Pinar et al, 2005;Tubbs et al, 2002) that revealed the details of the anatomy of the region. In details, Tubbs et al (2002) injected red and blue latex into the arteries and veins of twelve human cadavers (8 males and 4 females) found the primary arterial supply to the sympathetic chain and ganglia were from superior to inferior the ascending pharyngeal, ascending cervical, thyrocervical trunk, and supreme intercostals arteries.…”
Section: Discussionmentioning
confidence: 99%